The effect of seasonal variations on food consumption, dietary habits, anthropometric measurements and serum vitamin levels of University Students - Kucukerdonmez, Ozge; Rakıcıoglu, Neslisah (Progress in Nutrition, 2018)
Aim: The aim of this study was to examine the effect of seasonal variations on the dietary habits, food consumption, anthropometric measurements, physical activity and some serum vitamin levels of adult females. Methods:The study was conducted during consecutive four seasons in October (autumn), January (winter), April (spring), and July (summer). After general information was obtained about the participants via questionnaire, their anthropometric measurements were taken, and individual records kept for 7-day individual food consumption and 3-day physical activity. Also, their body compositions (Body Stat 1500Ò) and resting metabolic rates (Ergospirometry-Cosmed K4b2) were measured. Participant serum samples were analyzed for levels of vitamins A, E, β-carotene and 25-OH Vitamin D3. Subjects: Thirty-five healthy, young adult females between the ages of 19 and 24 were invited into a prospective research study. Results: Spring was found to be the season with the highest intake of energy and nutrients compared with other seasons (p<0.05). A significant (p<0.05) decrease in the values of body weight and body mass index was found in summer compared to spring and winter, and in autumn compared to winter. A decrease in the values of body fat mass (kg) and an increase in the values of fat-free mass (kg) were found in summer compared to winter (p<0.05) using bioelectrical impedance analysis. A significant decrease in the values of body water (L) was measured in spring, autumn and winter compared to summer (p<0.05). The value of energy expended due to physical activity increases in summer compared to spring and autumn, while the value of resting metabolic rate measured through ergospirometry decreases in summer compared to winter (p<0.05). It was determined that the level of serum vitamin A decreased in summer compared to autumn and spring, the level of vitamin D increases in summer while it decreases in winter, and the level of β-carotene increases in winter compared to other seasons (p<0.05). No significant difference was found between serum vitamin E levels of individuals between seasons (p>0.05). A significant positive correlation was determined between the levels of serum β-carotene and dietary β-carotene intake in autumn (r = 0.37, p<0.05). Conclusion: It was concluded that seasonal variations have significant effect on the nutritional status, body weights and compositions, daily energy expenditures, and particular serum vitamin levels in individuals. This should be taken into consideration when developing individual nutrition plans and establishing nutrition policies in Turkey, where all four seasons are experienced conspicuously.